2014
DOI: 10.1007/s12275-014-4416-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates mycobacterial proteasome

Abstract: Mycobacterium tuberculosis possesses a proteasome system that is required for the microbe to resist elimination by the host immune system. Despite the importance of the proteasome in the pathogenesis of tuberculosis, the molecular mechanisms by which proteasome activity is controlled remain largely unknown. Here, we demonstrate that the α-subunit (PrcA) of the M. tuberculosis proteasome is phosphorylated by the PknB kinase at three threonine residues (T84, T202, and T178) in a sequential manner. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…For example, several subunits of the 20S CP are known to be phosphorylated. Phosphorylation of the α-subunit in the Mycobacterium tuberculosis proteasome impedes assembly of the proteasome complex and consequently enhances mycobacterial resistance to H 2 O 2 (50). PKA phosphorylates several subunits of the mammalian 20S CP, including α1-α3, β2, β3 and β7, thus increasing the proteasomal chymotryptic and PGPH activities (51).…”
Section: Regulation and Underlying Molecular Mechanisms Of Proteasomementioning
confidence: 99%
“…For example, several subunits of the 20S CP are known to be phosphorylated. Phosphorylation of the α-subunit in the Mycobacterium tuberculosis proteasome impedes assembly of the proteasome complex and consequently enhances mycobacterial resistance to H 2 O 2 (50). PKA phosphorylates several subunits of the mammalian 20S CP, including α1-α3, β2, β3 and β7, thus increasing the proteasomal chymotryptic and PGPH activities (51).…”
Section: Regulation and Underlying Molecular Mechanisms Of Proteasomementioning
confidence: 99%
“…As the name indicates, this phenomenon shall be a generic one which has also been observed in cold atom systems [39]. This phenomenon is driven by the "force" along the radial direction which could be explicit derived in the Heisenberg equation [43]. In such a slowly rotating system, technically the condensate profile is supposed to be mainly induced by the ∂ω/∂r.…”
Section: Arxiv:190100804v1 [Nucl-th] 24 Dec 2018mentioning
confidence: 84%
“…Moreover, β1, the variant identified in this current study, has been reported to promote anti-apoptotic activity of plasminogen activator inhibitor 2 (PAI2) [75]. While the consequences of the phosphorylation of this subunit are unclear, it has been shown that phosphorylation of β-subunits in the prokaryote M. tuberculosis can inhibit proteasomal assembly [76]. While there are multiple β-subunits in eukaryotes, unlike in prokaryotes that have only one type, the reduced phosphorylated states in the oldest NMR brains could suggest that there is an increased affinity towards proteome assembly and therefore, an increased degradation of unwanted or damaged proteins, clearing the cell of detritus to promote healthy cellular function.…”
Section: Discussionmentioning
confidence: 97%